حساب عناصر محاور السكك الحديدية والطرق بطريقة المحطات المتتالية - لبابيدي عبد الرحمن بكري (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم هذا العمل طريقة لحساب الإحداثيات الديكارتية لمختلف عناصر محاور السكك الحديدية والطرق من خلال استخدام التكامل العددي. حيث يمكن حساب إحداثيات مختلف عناصر المحور (كلوتوئيد بسيط- كلوتوئيد بيضوي- كلوتوئيد متعاكس- منحني دائري- قطعة مستقيمة) في كل الحالات (اعتبارا من بداية المنحني أو من نهايته) وكل أنظمة الإحداثيات (عن طريق إدخال الإحداثيات العامة لنقطة البداية وميل المنحني في هذه النقطة) بواسطة برنامج حاسوبي واحد. This study presents a method to compute Cartesian coordinates of single points of alignments is described, using formulas of numerical integration. It is possible to determine immediately straight lines, circles and klothoides as transition curves in any arrangement (from the Startpoint or Endpoint of the Curve) and any coordinate system (by using the Coordinate of Startpoint and the Curvetangente in this point) by one single computing algorithm. A computing program under Matlab 5.3 is put, and testing examples are run, and the results are in the bottom.